Front and Back Matter for Volume 2 Issue 5, September 2025 - Trends in General Medicine and Public Health, Svāsthya (Svāsthya: Trends in General Medicine and Public Health, 2025)
Volume 2, Issue 5, September 2025 This issue consists of 5 articles contributed by 23 authors affiliated with 12 affiliations from four countries including Indonesia (Sekolah Tinggi Ilmu Kesehatan Medistra Indonesia, Universitas Gorontalo, Universitas Tompotika Luwuk, Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, dan Rumah Sakit Ibu dan Anak (RSIA) Pemerintah Aceh), Republic of Korea (Yonsei University), Timor-Leste (National Institution of Public Health Timor-Leste - INSP-TL)